The Role of Troops Raising the National Heritage Flag of the Republic of Indonesia in Forming Youth Nationalism (1946-1973) - Nurmeida, Dwi Azizatul; Nurhasanah, Ana; Fauzan, Rikza (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
This study aims to find out The Role of National Flag Raisers in Indonesia to Forming Youth Nationalism (1946-1973) based on critical reviews in the national press. The research method used is the historical method which consists of heuristics (data collection), source criticism, interpretation, and historiography using the theory of nationalism. The results of the study found that Paskibraka had been formed since the Indonesian Independence Day in 1946 in Yogyakarta. The participants selected were students currently studying in Yogyakarta. The enthusiasm of the people, especially the youth who come from various regions in Indonesia, shows that the sense of nationalism was initially regional in nature. However, the raising of the heritage flag on the Indonesian Independence Day every year creates a sense of youth nationalism. Paskibraka's more fundamental role is to shape the character of the Indonesian youth to become youth who have a sense of nationalism in accordance with Pancasila.